One‐pot self‐assembled TiO2/graphene/poly(acrylamide) superporous hybrid for photocatalytic degradation of organic pollutants. Issue 5 (13th August 2018) - Zeng, J.; Peng, C.; Wang, X.; Wang, R.; Zhang, N.; Xiong, S.
ABSTRACT: We report the development of TiO2 /graphene/poly(acrylamide) superporous hybrid by a radical polymerization reaction and explore its environmental application as photocatalyst of organic pollutants. During the polymerization reaction, graphene nanosheets and TiO2 nanoparticles homogeneously distribute on the hydrogel, in which TiO2 nanoparticles with a uniform size are densely anchored onto graphene and self‐assembled into different structures with various graphene contents. The resultant TiO2 /graphene/poly(acrylamide) superporous hybrid experiences tremendous adsorption toward dye pollution before photodegradation, and it also displays similar photodecomposition efficiency with pristine TiO2 . Moreover, the TiO2 /graphene/poly(acrylamide) superporous hybrid is recyclable, which demonstrates the potential of hybrid as an attractive photocatalyst for wastewater treatment. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47033. Abstract :